2017
DOI: 10.1016/j.polymdegradstab.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of polydicyclopentadiene oxidation

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. b s t r a c tThe in situ thermal oxidation of thin unstabilized polydicyclopentadiene was studied by TGA to monitor mass gain, and DSC to characterize hydroperoxides concentration. Results were discussed using kinetic analysis, which allowed the estimation of activation energies for key reactions of the oxidation process. Activation energy for termination was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 58 publications
3
34
1
Order By: Relevance
“…Figure b depicts the hydroperoxide concentration (mol kg −1 ) over time; initially, hydroperoxide content increases rapidly in the first week reaching a maximum of 1.73 mol kg −1 at 7 d before slowly decreasing to half of its original level at the last time point collected, day 65. Other studies investigating thin films of polyDCPD exhibit similar trends, a peroxide maximum followed extended period of decrease, if only at shorter time‐scales due to utilization of higher temperatures and/or pure oxygen atmospheres . Temperature and atmospheric composition plays an important role in the kinetics and accumulation of peroxide species in pDCPD networks .…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Figure b depicts the hydroperoxide concentration (mol kg −1 ) over time; initially, hydroperoxide content increases rapidly in the first week reaching a maximum of 1.73 mol kg −1 at 7 d before slowly decreasing to half of its original level at the last time point collected, day 65. Other studies investigating thin films of polyDCPD exhibit similar trends, a peroxide maximum followed extended period of decrease, if only at shorter time‐scales due to utilization of higher temperatures and/or pure oxygen atmospheres . Temperature and atmospheric composition plays an important role in the kinetics and accumulation of peroxide species in pDCPD networks .…”
Section: Resultsmentioning
confidence: 58%
“…Over a period of two months thermal analysis and gravimetric measurements of pDCPD 89 foams were performed as the samples aged under ambient conditions. Figure a indicates an average percent mass increase of 38% for pDCPD 89 foams due to the accumulation of oxygen species, with the majority of the increase occurring in the first 10 d. Previous work by Defauchy et al and Richaud et al demonstrated that hydroperoxide content of polymers, including polyDCPD, may be measured using DSC . During heating, the decomposition of hydroperoxide has a characteristic exotherm centered at 140 °C (Figure S5, Supporting Information); the concentration of hydroperoxide in the foam could be ascertained by integrating this exotherm and dividing by the decomposition enthalpy (Δ H OOH = ≈440 kJ mol −1 ) .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations